2016
DOI: 10.1002/jqs.2833
|View full text |Cite
|
Sign up to set email alerts
|

Glacial Lake Pickering: stratigraphy and chronology of a proglacial lake dammed by the North Sea Lobe of the British–Irish Ice Sheet

Abstract: We report the first chronology, using four new optically stimulated luminescence dates, on the sedimentary record of Glacial Lake Pickering, dammed by the North Sea Lobe of the British-Irish Ice Sheet during the Dimlington Stadial (24-11 ka cal BP). Dates range from 17.6 AE 1.0 to 15.8AE 0.9 ka for the sedimentation of the Sherburn Sands at East Heslerton, which were formed by multiple coalescing alluvial fans prograding into the falling water levels of the lake and fed by progressively larger volumes of debri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
57
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 40 publications
(60 citation statements)
references
References 65 publications
3
57
0
Order By: Relevance
“…Pickering (Evans, et al, 2016). These authors suggested that the Vale of York ice lobe extended briefly at about 18.7 ka to the south of the River Humber to reach Lindholme before retreating northwards to form the recessional Escrick and York moraines.…”
mentioning
confidence: 99%
See 4 more Smart Citations
“…Pickering (Evans, et al, 2016). These authors suggested that the Vale of York ice lobe extended briefly at about 18.7 ka to the south of the River Humber to reach Lindholme before retreating northwards to form the recessional Escrick and York moraines.…”
mentioning
confidence: 99%
“…1915; Kendall, 1893Kendall, ,1902Gaunt, 1976Gaunt, , 1981Powell et al, 1992;Frost, 1998;Thomas, 1999;Evans et al 1995;Boston et al, 2010;Evans and Thompson, 2010;Roberts et al, 2013;Busfield et al, 2015;Bateman et al, 2015;Evans et al, 2016). In the late 19 th century the primary geological survey mapped till (or 'boulder clay' as it was then described) in the Vale of York and along the Yorkshire coast (Fox-Strangways et al, 1885, 1886FoxStrangways and Barrow, 1915).…”
mentioning
confidence: 99%
See 3 more Smart Citations